Managing Change in Pluralistic Organizations: The Role of Normative Accountability Assumptions - Asad Mir, Farzana (2020)
Pluralistic organizations face the challenge of managing the co existence of multiple sets of assumptions associated with each institutional logic. This multiplicity of assumptions problematizes the findings from the change management literature that for successful change management, the normative assumptions of the change initiative should be congruent with the organizational normative assumptions. One of the organizational mechanisms in which the normative assumptions are encoded and enacted is the system of accountability, hence in pluralistic organizations, there is a need to understand the role of the interplay of the normative accountability assumptions of the change initiative with the multiple sets of accountability assumptions representing individual logics within the organization. This study examines the case of a project to renew a strategic framework of a Canadian public university. The project diverged from the existing governance practices and their associated accountability assumptions that represented the institutional logic of managerialism. We found that this project was widely accepted, despite deviating from the institutional logic that supported existing practices, because its accountability assumptions were congruent with co-existing and deeply-rooted, democratic logic within the organization. Our f indings contribute to the change management literature by highlighting the role of normative accountability assumptions in change management within pluralistic organizations.